Approximately inner derivations - Bratteli, Ola; Kishimoto, Akitaka; Robinson, Derek W. (MATHEMATICA SCANDINAVICA, 2008)
Let $α$ be an approximately inner flow on a $C^*$-algebra $A$ with generator $δ$ and let $δ_n$ denote the bounded generators of the approximating flows $α^{(n)}$. We analyze the structure of the set 26739 \mathcal D=\bigl\{x\in D(δ): \lim_{n→∞}δ_n(x)=δ(x)\bigr\} 26739 of pointwise convergence of the generators. In particular we examine the relationship of $\mathcal D$ and various cores related to spectral subspaces.